Inflation Targeting and Fiscal Rules : Do Interactions and Sequencing Matter? - Combes, Jean-Louis (IMF Working Papers; Working Paper, 2014)
The paper examines the joint impact of inflation targeting (IT) and fiscal rules (FR) on fiscal behavior and inflation in a broad panel of advanced and developing economies over the period 1990-2009. The main contribution of the paper is to show that, as suggested by the theoretical literature, interactions between FR and IT matter a great deal for policy outcomes. Specifically, the combination of FR and IT appears to deliver more disciplined macroeconomic policies than each of these institutions in isolation. In addition, the sequencing of the monetary and fiscal reforms plays a role: adopting FR before IT delivers stronger results than the reverse sequence.